2‐Deoxy‐d‐Glucose Sensitizes Human Ovarian Cancer Cells to Cisplatin by Increasing ER Stress and Decreasing ATP Stores in Acidic Vesicles. Issue 12 (4th August 2015) - Zhang, Lili; Su, Jing; Xie, Qi; Zeng, Linchuan; Wang, Yan; Yi, Dan; Yu, Yang; Liu, Shibing; Li, Songyan; Xu, Ye
ABSTRACT: Cisplatin is a commonly used chemotherapeutic agent; however, the development of acquired resistance limits its application. Here, we demonstrate that 2‐deoxy‐d ‐glucose (2‐DG) enhanced the antitumor effects of cisplatin in SKOV3 cells, which include inhibition of proliferation and promotion of apoptosis. Additionally, either cisplatin or 2‐DG alone could upregulate the endoplasmic reticulum (ER) stress‐associated protein glucose‐regulated protein‐78 (GRP78). Moreover, exposure to 2‐DG increased the expression of GRP78 induced by cisplatin. Cisplatin also upregulated ER stress‐associated apoptotic protein 153/C/EBP homology protein (CHOP) in SKOV3 cells. While treatment with 2‐DG alone could not upregulate the CHOP expression, a combination of both 2‐DG and cisplatin increased the protein levels of CHOP above those induced by Cisplatin alone. Finally, cisplatin mediated an increase in ATP stores within acidic vesicles, whereas 2‐DG decreased this effect. These data demonstrate that 2‐DG sensitizes SKOV3 cells to cisplatin by increasing ER stress and decreasing ATP stores in acidic vesicles.